Use of disease-modifying anti-rheumatic or anti-tumour necrosis factor drugs and risk of hospitalized infection in ankylosing spondylitis. (4th March 2019) - Moura, CS; Rahme, E; Maksymowych, WP; Abrahamowicz, M; Bessette, L; Bernatsky, S
Abstract : Objective : To assess the risk of hospitalized infection among initiators of disease-modifying anti-rheumatic drugs (DMARDs) and/or anti-tumour necrosis factor (anti-TNF) agents in ankylosing spondylitis (AS). Method : We studied AS patients, new users of anti-TNF drugs and/or DMARDs between 1 January 2001 and 31 December 2011. Cohort entry was defined as the date of first prescription of any of these drugs. We used Cox regression with three time-varying drug exposures: current use of DMARDs without biologics, current use of anti-TNF agents alone or in combination with DMARDs (anti-TNF ± DMARDs), and current non-use. Models were adjusted for baseline patient sociodemographic characteristics, comorbidity, outpatient visits and procedures, previous infection, non-steroidal anti-inflammatory drugs, and corticosteroids. Hospitalized infection was defined on the basis of hospitalization discharge diagnoses (primary or non-primary) coding for infection. Results : The cohort included 747 AS patients, with a mean age of 51.1 years (sd 14.6), and 466 (62.4%) were men. During the median follow-up of 1.98 years, 57 hospitalized infections occurred, for an incidence rate of 2.9/100 person-years. The adjusted hazard ratio of infection (relative to unexposed) was 1.00 [95% confidence interval (CI) 0.47–2.11] for the anti-TNF ± DMARDs group and 0.96 (95% CI 0.45–2.04) for DMARDs alone. Use of healthcare, corticosteroids, and previous hospitalized infections were associated with infection. Conclusion : We found no clear evidence that the risk of hospitalized infection was linked to DMARD and/or anti-TNF drug use. Because of scarce published literature on infection risk in AS patients, our results have important implications for clinicians.